Direct Costs of Epidermolysis Bullosa by Disease Severity - Darragh Flannery; Claire Doyle; Sineád Hickey; Fiona Aherne; Avril Kennan (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)